Digital info-inclusion in the city of marília: A proposal of an instructional technology program - Da Costa Santos, Plácida L. V. Amorim [UNESP]; Do Prado, Ricardo P. [UNESP]; Jorente, Maria José Vicentini [UNESP] (ACTA Press, 2011)
In the process of Brazil's entry into the Information Society, citizen's education in this field is vital in order to the individuals to act and live in equal opportunities and conditions. The information and communication technologies (ICT) can offer enormous contribution to the effectiveness and visibility of the programs of digital infoinclusion, increasing numbers with regards to people, communities and regions. This article reports on strategies developed, and measures implemented by the City department of Education for the municipal government schools in the city of Marilia, São Paulo. An epistemological and practical orientation is adopted. As a result, one identifies, in a digital environment, a guarantee of better conditions of the informational development of the competences of the citizens involved. The project Instructional Technology Program consolidated a perception of the necessity of partnerships that lead to improved results on the use of computer science technology by students of basic education according to evaluations and national competitions. Partnerships among teachers and post-graduates in Information Science at the Marília campus of UNESP (Sao Paulo State University) the City department of Education, instructors of computer science training, and teachers of the municipal schools, will contribute to give visibility to situations that still defy and affect the programs of digital inclusion in the municipal public administration.
Keywords: Digital inclusion; Information and communication technologies (ICT); Information and Technology; Media